2017
DOI: 10.1111/rda.12934
|View full text |Cite
|
Sign up to set email alerts
|

The effect of some cryoprotectants on dromedary camel frozen‐thawed semen

Abstract: The cryopreserved camel semen is often associated with poor quality and fertility. This study aimed to improve the dromedary frozen semen quality by comparing the efficiency of four cryoprotectant agents (CPAs) on sperm freezability. Semen samples were collected from seven male Maghrabi camels, diluted with Shotor diluent supplemented with glycerol (Sh-G), dimethyl formamide (DMF, Sh-DF), dimethyl sulfoxide (DMSO, Sh-DS) or ethylene glycol (EG, Sh-EG), all at 6% final concentration, and the samples were subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
7
2
Order By: Relevance
“…Although different AV types or modifications are currently in use, no exhaustive research into the most suitable one has been performed. For instance, El-Badry et al (2017) and Ziapour et al (2014) used a 30 cm long AV with a 5 cm inner diameter and a foam cervix imitation (according to indications by Bravo et al, 2000), whereas El-Bahrawy, in 2010, used the same kind of AV without the cervix imitation. Since it is believed that sperm motility could be affected by contact with the AV rubber or with the AV collection funnel, all the above authors applied a plastic liner inside the AV cylinder (El-Badry et al, 2017;El-Bahrawy, 2010;Ziapour et al, 2014).…”
Section: Mating Behaviour and Semen Parameters In Dromedary Camel Bulmentioning
confidence: 99%
See 1 more Smart Citation
“…Although different AV types or modifications are currently in use, no exhaustive research into the most suitable one has been performed. For instance, El-Badry et al (2017) and Ziapour et al (2014) used a 30 cm long AV with a 5 cm inner diameter and a foam cervix imitation (according to indications by Bravo et al, 2000), whereas El-Bahrawy, in 2010, used the same kind of AV without the cervix imitation. Since it is believed that sperm motility could be affected by contact with the AV rubber or with the AV collection funnel, all the above authors applied a plastic liner inside the AV cylinder (El-Badry et al, 2017;El-Bahrawy, 2010;Ziapour et al, 2014).…”
Section: Mating Behaviour and Semen Parameters In Dromedary Camel Bulmentioning
confidence: 99%
“…For instance, El-Badry et al (2017) and Ziapour et al (2014) used a 30 cm long AV with a 5 cm inner diameter and a foam cervix imitation (according to indications by Bravo et al, 2000), whereas El-Bahrawy, in 2010, used the same kind of AV without the cervix imitation. Since it is believed that sperm motility could be affected by contact with the AV rubber or with the AV collection funnel, all the above authors applied a plastic liner inside the AV cylinder (El-Badry et al, 2017;El-Bahrawy, 2010;Ziapour et al, 2014). Skidmore et al (2013) reported that the disposable inner liner was not well accepted by the bulls, and Cholakkal et al, (2016) reported that the use thereof was unsuitable because the collected ejaculates 'stick' to the liner, were 'frothy' and of low volume.…”
Section: Mating Behaviour and Semen Parameters In Dromedary Camel Bulmentioning
confidence: 99%
“…They determine the efficiency of cryopreservation protocols and thus play a key role in semen protection [5]. Therefore, numerous efforts have been made to define the best semen extender in different animal species including Camelidae [6,7,8]. These efforts ended with the formulation of many commercial semen extenders for bovine and equine, while for camelids there are mainly two specific semen extenders SHOTOR and Green buffer.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts ended with the formulation of many commercial semen extenders for bovine and equine, while for camelids there are mainly two specific semen extenders SHOTOR and Green buffer. SHOTOR has proven successful in the preservation of both chilled and frozen Bactrian camel semen [9,10] as well as dromedary camel semen [6]. Moreover, Green buffer has proven successful in the preservation of frozen dromedary camel semen [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation